Monopsony Makes Firms Not Only Small but Also Unproductive: Why East Germany Has Not Converged - Rüdiger Bachmann; Christian Bayer; Heiko Stüber; Felix Wellschmied (Institute of Labor Economics (IZA), 2022)
When employers face a trade-off between growing large and paying low wages—that is, when they have monopsony power—some productive employers will decide to acquire fewer customers, forgo sales, and remain small. These decisions have adverse consequences for aggregate labor productivity. Using high-quality administrative data from Germany, we document that East German plants (compared to West German ones) face a steeper size-wage curve, invest less into marketing, and remain smaller. A model with labor market monopsony, product market power, and customer acquisition matching these features of the data predicts 10 percent lower aggregate labor productivity in East Germany.
Keywords: E20; E23; E24; J20; J42; J50; 330; aggregate productivity; plant heterogeneity; unions; monopsony power; size-wage curve; monopolistic competition; customer capital; size distortions